Literature review: The impact of artificial intelligence on employee productivity and performance - Abdurrahim Abdurrahim (International Journal of Applied Finance and Business Studies, 2025)
This study aims to comprehensively examine the impact of Artificial Intelligence (AI) implementation on employee productivity and performance in various sectors. The method used is a narrative literature review that analyzes the results of empirical and theoretical studies related to AI and human resource performance, with data sources from relevant journals and recent research. The results of the study show that AI can increase operational efficiency through automation and fast data processing, as well as improve the quality of decision-making that has a positive impact on employee work performance. Psychological factors such as technology acceptance and readiness to adapt and employee digital literacy competencies are the keys to the success of AI implementation. In addition, employee involvement acts as a strategic mediator that optimizes AI's contribution to productivity. The implications of this study emphasize the importance of synergy between technological innovation and strengthening human capital to support sustainable organizational digital transformation. This study fills the research gap by integrating technical and social perspectives in measuring the impact of AI on employee performance and providing a more holistic and multidimensional research direction. This research also offers important practical contributions and policy implications for managers and policy makers in optimizing the implementation of AI to achieve better organizational performance.